The Crisis of Ethics in Public Officials' Communication Language in the Context of Nationalism and Governance - Mutadayyinah, Yuni; Dinda Nadia, Fiona Niska; Faiz, Achmad Zaky (UIN Fatmawati Sukarno Bengkulu, 2025)
The language of communication of public officials represents ethics, morality, and responsibility in maintaining national stability and government legitimacy. However, recently, there has been a frequent phenomenon of language ethics crisis, characterized by controversial, discriminatory speech, and even containing elements of hate speech. This study aims to analyze the crisis of language ethics in public officials' communication from the perspective of nationalism and governance. The novelty of this study lies in the relational analysis between the language ethics of public officials and the value of nationalism in the context of democratic governance. This study emphasizes the importance of fostering communication ethics based on Pancasila values and the principles of ethical political communication. The method used is library research by reviewing literature, scientific articles, and credible news related to the issue of communication ethics of public officials in Indonesia. Researchers use communication ethics theory to analyze data. The results of the study indicate that the crisis of language ethics has an impact on weakening public trust, decreasing state authority, and has the potential to trigger social disintegration. The crisis of public officials' language ethics is not only a linguistic issue, but is also closely related to the legitimacy of government and the integrity of nationalism. Abusive, discriminatory, or provocative language not only undermines communication ethics but also undermines national unity and government legitimacy. This research demonstrates that public officials need to internalize communication ethics based on moral values, Pancasila, and democratic principles to maintain national dignity.